Implications of Macroeconomic Variables on Financing Performance and Profitability of Sharia Banking Before and During Covid-19 Pandemic - Febriany, Lulu (Budapest International Research and Critics University, 2021)
In the midst of the uncertainty of the COVID-19 pandemic, it has had a severe impact on the health side and has an impact on the world economy. Not a few companies in various sectors have started and survived, whether they are strong or not defending their companies. One of them is the Islamic banking sector. This study tries to examine how the implications of macroeconomic variables on the financing performance and profitability of Islamic banking are influential or not. Macroeconomic variables consisting of independent variables are X1 is inflation, X2 is interest rates, X3 is exchange rate, X4 is GDP, and the dependent variable is Y1 is financing performance and Y2 is Islamic banking profitability.